PERANCANGAN MANAJEMEN RISIKO DI SEBUAH PERUSAHAAN FURNITURE - Selly Hartawan (Jurnal Titra, 2016)
The article discusses an identification of the risk at a furniture company. Risk identification was done at 44 departments which are consist of Division of P1, P2, P5 and Supporting Department. Risk management form (RM) and Failure Mode Effect Analysis (FMEA) are used to identify the risk, by doing some interviews and using questionnaires. The result shows there are 238 risk priorities. There are 71% of risk at Division P1, 3% risk at Division P2, 1% risk at Division P2, 24% risk at Supporting Department that must be prioritized.